1997
DOI: 10.1083/jcb.138.1.65
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Class of RanGTP Binding Proteins

Abstract: The importin-α/β complex and the GTPase Ran mediate nuclear import of proteins with a classical nuclear localization signal. Although Ran has been implicated also in a variety of other processes, such as cell cycle progression, a direct function of Ran has so far only been demonstrated for importin-mediated nuclear import. We have now identified an entire class of ∼20 potential Ran targets that share a sequence motif related to the Ran-binding site of importin-β. We have confirmed specific RanGTP binding for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
421
0
6

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(439 citation statements)
references
References 80 publications
(168 reference statements)
10
421
0
6
Order By: Relevance
“…The similarity is higher in the N-terminal half, which mediates RanGTP binding (20). A similar repetitive pattern with a loose consensus of hydrophobic residues can be identified in all the sequences.…”
Section: -4)mentioning
confidence: 68%
“…The similarity is higher in the N-terminal half, which mediates RanGTP binding (20). A similar repetitive pattern with a loose consensus of hydrophobic residues can be identified in all the sequences.…”
Section: -4)mentioning
confidence: 68%
“…The following proteins were expressed in E. coli BLR/Rep4 and purified as described in the literature indicated: Xenopus importin ␣ (29), human importin ␤ (30), transportin (21), Xenopus importin 7, and importin 5 (28). Expression and purification of Ran, RanQ69L(GTP), NTF2, L23a 2z and 4z fusion proteins, the IBB-6z fusion protein, and the M9-GST fusion protein was performed as described (13,14).…”
Section: Methodsmentioning
confidence: 99%
“…Because, for example, Imp␤ and Imp7 are able to form heterodimers (28), Imp␤ retained by the histone matrix can be bound by Imp7 and thus may incorrectly indicate the binding of Imp7 to the histone. To assess whether direct binding of Imp␤ and Imp7 occurs in vitro, we performed binding experiments with recombinant Imp␤ and Imp7.…”
Section: Fig 1 the Imp␤-imp7 Heterodimer Is The Only Functional Impmentioning
confidence: 99%
“…Nucleocytoplasmic transport is mediated largely by the superfamily of transport receptors that interact with nuclear pore complexes (NPCs), share an N-terminal RanGTP-binding motif and are related to importin ␤ (8,9). CRM1 binds its cargo in the nucleus, translocates it to the cytoplasm, releases the cargo, and returns back to the nucleus.…”
mentioning
confidence: 99%
“…Within Rev, the region Leu-64 to Arg-80 was protected by CRM1, whereas Rev specifically interacts with residue Asp-716 and the neighborhood of Lys-810 of CRM1 (17). RanGTP binding to CRM1 is expected to be mediated by a region near the N terminus (8,9). A comparison of leucine-rich NESs of several proteins revealed that the Rev NES has a relatively low affinity for CRM1 (18).…”
mentioning
confidence: 99%